Perbandingan Efi kasi dan Efek Samping Antara Albendazol, Albendazol-Levamisol dan Mebendazol-Levamisol Terhadap Infeksi Soil-Transmitted Helminths pada Anak Usia Sekolah Dasar Negeri Kabupaten Deli Serdang - Endy Julianto (Fakultas Farmasi Universitas Pancasila, 2017)
Intestinal worm infection in particular of Soil Transmitted Helminth is still a global problem with high prevalence on the tropic and subtropic regions including Indonesia especially in the rural community. Double Blind Randomized Trial that started from April to June 2015 in which the samples are collected from public elementary school children on the Deli Serdang Regency to compare the effectivity and side effect of STH infection treatment by using Albendazole 400 mg, Albendazole 400 mg-Levamisol 50 mg/100 mg, Mebendazole 500 mg-Levamisol 50 mg/100 mg. The samples of Albendazole, Albendazole-Levamisol and Mebendazole-Levamisol groups consist of 60 children in each group in which the ones that have STH infection are Ascariasis 92 children 51.11%, Trichuriasis 37 children 20.55%, and mixed infection 51 children 28.33%. In this research, researcher doesn’t found hookworm infection in any of the groups. From the result ofstool examination, researcher found 100% of cure rate for A. lumbricoides infection on all groups, cure rate of T. trichiura infection 66.7%, 94.7%, 92.3% for each Albendazole, Albendazole-Levamisol, and Mebendazole-Levamisol groups meanwhile cure rate for mixed infection are 28.6%, 85.7%, and 66.7% for each Albendazole, Albendazole-Levamisoland Mebendazole- Levamisol groups. For mild T.trichiura infection treatment with singledose of Albendazole-Levamisolgroup is better than both of Albendazole and Mebendazole- Levamisole groups (p=0.01). In this research, researcher found nausea and diarrhea as treatment of side effect and no signifi cant difference of side effect in all groups of treatment.